Understanding Jimintō (Liberal Democratic Party) factionalism as a structure of elite circulation in Japanese politics - Akçevin, Yalın. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
The factions of the Liberal Democratic Party of Japan (Jimintō/LDP) have been subjected to different analyses over the years, each seeking to explain their origins and functions, and to forecast their future. Factions have been studied from cultural and functional-structural viewpoints, and have been characterized as being integral to both the functioning and breakdown of the Japanese political system and the LDP. This study aims to expand the discussion on the factions by moving beyond both these existing viewpoints by using the works of Weber, Michels, Pareto, and Mosca, and by introducing a new model for attributing levels of significance to the circulation of elites. Thus, this study seeks to examine the changing power and influence of the factions as a structure that is integral to the cycle of elite circulation in Japanese politics. While doing so, this study also aims to reexamine the functions and significance of the factions and the Japanese Prime Minister as a factional representative from the viewpoint of elite theories, whilst locating the Japanese case as firmly outside the scope of Japanese exceptionalism as possible by comparing it to the case of Italy’s Democrazia Cristiana (DC). The findings indicate that the factions of the LDP have functioned as conflicting elite organizations with discernible policy involvements and differentiations. In addition, their powers have shifted in response to the needs of the party and the nation, producing the leadership changes necessary and ensuring that the political elites have been in a state of circulation within the LDP.
Keywords: Japan -- Politics and government -- 1945-